Banking in Sub-Saharan Africa : The Macroeconomic Context - Mlachila, Montfort (Departmental Papers; Departmental Paper ;, 2013)
Many countries in sub-Saharan Africa (SSA) have seen accelerated growth for an extended period of time since the mid-1990s, making a clear break with their long stagnant growth during the previous two decades. That said, the region faces significant challenges over the medium to long term, including reducing poverty, overcoming infrastructure bottlenecks, enhancing productivity and skill levels, and improving the business climate, among others. The banking sector remains underdeveloped in SSA, thus reducing its contribution to growth, although its limited integration with global financial markets helped countries weather adverse effects of the global financial crisis. It is imperative that the banking sector plays a more active role in SSA, in order to achieve sustainable growth led by the private sector. This paper, building on the recent literature on SSA, discusses the main features of the region's growth and macroeconomic performance in recent years and the outlook for the coming years; it then reviews the main features of SSA banking systems and how they were affected by the global economic crisis, while flagging some factors that could influence financial sector developments in SSA in the period ahead.